Evaluation of the Frequency and Pathological Diagnosis of Vulvar Lesions Is it Associated with Vulvar Pruritus - If So, How Closely? - Demir, Omer; Ozalp, Mirac; Aran, Turhan; Osmanagaoğlu, Mehmet Armagan (Gynecology Obstetrics & Reproductive Medicine, 2021)
OBJECTIVE: Vulvar lesions are not well known to gynecologists and often cause difficulties in the differential diagnosis. In this study; we aimed to show the frequency of pathologic diagnosis of vulvar lesions and their relationship with vulvar pruritus. STUDY DESIGN: The pathological results of the patients who underwent vulvar biopsy between 2015 and 2019 were examined. The frequency of vulvar lesions was determined and classified under certain headings for gynecologists. The pathological diagnoses were correlated with the severity of pruritus. RESULTS: A total of 220 patients underwent a vulvar biopsy between the dates indicated in the study. The mean age of these patients was 47.9±16.7. The most common concomitant lesion was vulvar pruritus with a rate of 62.7% in cases who were referred to the outpatient clinic and referred for vulvar biopsy. According to biopsy results, the three most common pathological diagnoses were proliferative lesions, infection, and dermatoses. Dermatoses were the most common pathologic diagnosis in patients with severe pruritus. CONCLUSION: Thanks to the clear classification of vulvar lesions for gynecologists; pathological diagnoses will not be overlooked and differential diagnoses will be more effective. In vulvar lesions accompanied by pruritus, making the differential diagnosis according to the severity of pruritus and bringing the possible diagnosis to mind first will speed up the treatment.